Analisis Semiotika Representasi Kecantikan Iklan Fair and Lovely Versi Jessica Mila di Media YouTube - Sindi Dwi Amara; Ayu Suryati; Ika Nabila Putri; Nadia Idris (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Semiotics Analysis of Beauty Representation in Jessica Mila's Fair and Lovely Advertisement on YouTube Media which aims to analyze, describe and find out the meaning of beauty advertisements brought by Jessica Mila based on icons, symbols, and also the index on Fair and Lovely YouTube ads using research on semiotics. The research method used in this research is descriptive qualitative research, while the focus in this study is to analyze the signs used in advertising. Data collection techniques in this study used documentation techniques and data analysis techniques using Peirce's theory (1955) which revealed that semiotics is a science that discusses signs and the meaning of their application. Based on the results of research and discussion, the representation of beauty in Jessica Mila's version of Fair and Lovely advertisement there are 20 signs and icons, 5 index signs, and 12 symbol signs.